ANALYSIS OF MATHEMATICAL CONCEPTUAL UNDERSTANDING IN SOLVING NUMBER PATTERN PROBLEMS AMONG EIGHTH-GRADE JUNIOR HIGH SCHOOL STUDENTS - Andi Mulawakkan Firdaus; Siti Rahaimah Binti Ali (Almeera Education, 2026)
Conceptual understanding is the foundation for mastering higher-order mathematical competencies, yet student achievement in number patterns remains suboptimal. This study aims to describe the mathematical conceptual understanding of eighth-grade students at SMP Negeri 5 Bulukumba in solving number-pattern problems, based on seven indicators of conceptual understanding. A descriptive design with a mixed-methods sequential explanatory model was employed. The research subjects were 23 students of class VIII B, selected through purposive intact-class sampling; six of them, consisting of two students in the very high category, two in the moderate category, and two in the very low category, were purposively selected for task-based interviews. Data were collected through a three-item essay test and one interview task, then analysed using descriptive statistics and the interactive analysis model of Miles, Huberman, and Saldana, with data validity examined through technique triangulation. The results show an average error rate of 32.56% across the seven indicators. The lowest error rate occurred on the indicator of restating a concept (19.5%), whereas the highest error rates occurred on the indicators of selecting particular procedures or operations and of applying concepts in problem solving, each at 39.1%. Nevertheless, the differences between indicators correspond to only one or two students, so the ordering of difficulty must be interpreted cautiously. Classical mastery reached only 43.48%, far below the minimum criterion of 80%. Interview data indicate that low-achieving students tend to manipulate only the numbers visible in the problem without selecting an appropriate procedure, and that indicator mastery is not strictly hierarchical.